Biomedical science lecture notes - Lyons, Ian (Ian J.) (Wiley-Blackwell, 2011)
"Written by students for students, Biomedical Science: Lecture Notes is a concise, full-color textbook providing a 'one-stop-shop' for biomedical science students. Corresponding broadly to the common integrative, systems-based approach taken by the majority of medical schools, it provides a concise, student-led approach that is rooted in clinical relevance. The book is filled with learning features such as key definitions and mnemonics and is extensively cross-referenced to develop interdisciplinary awareness. Designed predominantly for medical students, the book also is useful for students studying for dentistry, pharmacology and nursing courses"--Provided by publisher.